Mineral Resource Tenders and Mining Infrastructure Projects Guiding Principles - Stanley, Michael; Mikhaylova, Ekaterina (World Bank, Washington, DC, 2014)
Numerous recent changes in the mining industry have led governments to an increased interest in the tender process as a means of awarding mineral rights. High demand and high mineral prices driven by rapid economic growth in countries such as Brazil, China, and India, and the emergence of new global companies in these countries, have resulted in increased competition to obtain access to mineral resources worldwide. The two parts of this paper, the guidance/good practices and the case study, are presented together even though they do not directly draw on each other's conclusions. Both examine guiding principles and good practices for governments to use in attracting mineral investments. Although it is noted by the authors that the Aynak tender was not a perfect process, occurring as it did in a difficult environment with a deficient in-country capacity and myriad investment challenges, it is a relevant example of what is involved and what must be considered by a government in the process and content of a tender. The paper is expected to motivate long-term strategic thinking among decision makers in mineral-rich countries on ways to begin mine development with the end in mind. Its intention is not to prescribe a set of actions, but rather to inform possible ways of maximizing the local content from mining projects which will need to be adjusted in each unique case.